Effect of different hemodialysis ways on microinflammatory state in maintenance hemodialysis patients - PENG Zhi-yuan; WANG Jin-liang; SUN Zhan-shan; ZHANG Li-li; WANG Yan; BAO Si-qin; DAI Zhi-jie (Linchuang shenzangbing zazhi)
Objective To investigate the concentration changes of plasma nitrogen(BUN),serum creatinine(SCr),albumin(Alb),β2-microglobulin(β2-MG),interleukin-1(IL-1),interleukin-6(IL-6),C-reactive protein(CRP) and Procalcitonin(PCT),and understand the effects of different dialysis ways on microinflammation state in maintenance hemodialysis(MHD) patients.Methods Thirty-two cases undergoing MHD with the using of Fx80 polysulfone were selected as high flux hemodialysis(HFHD) group,and 28 patients with the using of F6 polysulfone served as hemoperfusion combined with hemodialysis patients(HP+ HD) group.Blood samples were collected to detect the levels of blood BUN,SCr,β2-MG,IL-1,IL-6,CRP,PCT and Alb.Results There was no significant difference in age,sex,duration of dialysis between two groups(P>0.05).There was no significant difference in the changes of BUN,SCr and Alb between two groups(P>0.05).There was significant difference in the changes of IL-1,IL-6,CRP,PCT,and β2-MG between two groups.Conclusions As compared with patients undergoing HP + HD,HFHD improves the micro-inflammatory state and quality of life,but does not significantly increase the economic burden on patients.